Posisi Ideologi Maskulinitas Fatherhood Dalam Film Bernuansa Islami “Hafalan Shalat Delisa” - Himawan, Hilmi; Rahardjo, Turnomo; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
Traditional, patriarchal masculinity has reinforced rigid, authoritarian male roles, often leading to emotional distance between fathers and their children. The advent of the information age has ushered in a new ideology of masculinity known as 'fatherhood', which emphasizes active involvement in family life and the cultivation of deeper emotional connections. This study examines the representation of fatherhood masculinity in the film "Hafalan Shalat Delisa" and analyzes the position of this ideology within the film. Specifically, it investigates whether traditional, patriarchal, and toxic masculinity persists within these representations. Employing John Fiske's semiotic analysis, the research will explore the signs and forms of representation within the film.